Assessing the Linkages of Livelihood Capitals of Small-Scale Fishermen in Malaysia - Nor Samsinar Kamsi; R. B. Radin Firdaus; Md Nazirul Islam Sarker; Mahinda Senevi Gunaratne (SAGE Open)
The adaptive capacity of small-scale fishermen (SSF) hinges on the interaction between multiple livelihood capitals—human, physical, social, financial, and natural—as outlined in the Sustainable Livelihood Framework. However, existing studies have primarily focused on individual aspects of these capitals, with limited attention to how they collectively shape adaptive capacity, particularly within the Malaysian context. This study addresses this gap by developing an Adaptive Capacity Index (ACI) and assessing the interrelationships among livelihood capitals for SSF in Kedah and Kelantan. Using stratified random sampling, 722 SSF were selected from nine fisheries areas, with data collected through structured surveys and analysed using PLS-SEM. Our findings indicate that financial and physical capital have the most significant impact on economic capital. Social capital affects outcomes related to natural capital but has a limited effect on human capital. The quality of physical capital is essential for marine conservation efforts and the resilience of SSF. ACI calculations show varying adaptive capacities across regions, implying the need for multidimensional adaptation strategies that address specific geographical challenges. Our findings also reveal how different types of capital act as compensatory mechanisms depending on a community’s resource constraints. SSF in Kedah must rely on their social networks when financial and physical resources are limited. In contrast, areas with well-developed natural and physical resources do not depend on financial capital. Substantial financial resources in some parts of Kelantan enhance overall adaptive capacity, while in others, they help compensate for natural resource loss and weak social ties.